A stability-indicating HPLC-PDA method for the determination of ferulic acid in chitosan-coated poly(lactide-co-glycolide) nanoparticles (Brazilian Journal of Pharmaceutical Sciences, 2017)
The development and validation of a simple and efficient method for the quantification of ferulic acid in poly (D,L-lactide-co-glycolide) (PLGA) nanoparticles coated with chitosan (CS) by reverse phase high performance liquid chromatography coupled to photodiode array detection was described. For the chromatographic analysis, a reverse phase C-18 column was used, mobile phase consisting of acetonitrile and 0.5% acetic acid (37:63, v/v), isocratically eluted at a flow rate of 1 mL/min. Drug determination was performed at 320 nm. The method was validated in terms of the selectivity, linearity, precision, accuracy, robustness, limits of detection and quantification. The method was linear in the range of 10 to 100 μg/mL (r=0.999) and presented limit of detection and quantification of 102 ng/mL and 310 ng/mL, respectively. The method was precise (intra and inter-day) based on relative standard deviation values (less than 3.20%). The recovery was between 101.06 and 102.10%. Robustness was demonstrated considering change in mobile phase proportion. Specificity assay showed no interference from the components of nanoparticles or from the degradation products derived from acidic and oxidative conditions. The proposed method was suitable to be applied in determining the encapsulation efficiency of ferulic acid in PLGA-CS nanoparticles and can be employed as stability indicating one.